Conflict and Colonialism in 21st Century Romantic Historical Fiction Repairing the Past, Repurposing History - Fresno-Calleja, Paloma; Fresno-Calleja, Paloma; Teo, Hsu-Ming (Taylor & Francis Routledge [Imprint], 2024)
This book explores how postmillennial Anglophone women writers use romantic narrativisations of history to explore, revise, repurpose and challenge the past in their novels, exposing the extent to which past societies were damaging to women by instead imagining alternative histories. The novelists discussed employ the generic conventions of romance to narrate their understanding of historical and contemporary injustice and to reflect upon women's achievements and the price they paid for autonomy and a life of public purpose. The volume seeks, firstly, to discuss the work of revision or reparation being performed by romantic historical fiction and, secondly, to analyse how the past is being repurposed for use in the present. It contends that the discourses and genre of romance work to provide a reparative reading of the past, but there are limitations and entrenched problems in such readings.
eng
Keywords: Biography, Literature and Literary studies; Colonialism and imperialism; History and Archaeology; History: specific events and topics; History; Literary studies: fiction, novelists and prose writers; Literature: history and criticism; alternative histories; Caribbean Historical Romance; Caribbean Literature; Conflict and Colonialism in 21st Century Romantic Historical Fiction; Her Land; Her Love; historical and contemporary injustice; Historical Romance; Holocaust Literature; Hsu-Ming Teo; Navajo; Pacific War; Paloma Fresno-Calleja; Parsons Yazzie; Plantation Life; postmillennial Anglophone women writers; Quaker; romance; romantic historical fiction; romantic narrativisations of history; Routledge Research in Women's Literature; Sarah Lark; Sexual Justice; Suffragette; The Faithless Wife; the Spanish Civil War; US Civil War; Women's Suffrage